Molecular diversity of Mycobacterium tuberculosis isolates in Treatment-experienced Patients from Andhra Pradesh, India - Anagoni Srikar; Banda Venkataramana; Alladi Mohan; PVGK Sarma; Kangjam Rekha Devi; Kanwar Narain; Abhijit Chaudhury (Journal of Infection in Developing Countries)
Introduction: To get a comprehensive idea about the transmission and epidemiology of TB globally and locally, the use of molecular typing methods has become imperative not only for understanding genetic diversity but also the population structure of Mycobacterium tuberculosis complex (MTBC). We aimed to investigate the drug resistance pattern and genetic diversity of MTBC among previously treated patients with sputum smear-positive pulmonary tuberculosis in a South Indian population.